DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP KEBIASAAN BELAJAR MAHASISWA PROGRAM PENDIDIKAN TEOLOGI DI UNIVERSITAS ST. PAULUS RUTENG - Aprilianus Pala; Elisabet Gergosiani Juita; Frasiskus Sales Lega (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
The development of information technology today has brought about major changes in the way humans communicate and learn. Social media such as Instagram, WhatsApp, TikTok, and Facebook are now an integral part of student life, including students in the Theology Education Program at St. Paulus Ruteng University. This study aims to describe the impact of social media use on the learning habits of students in class 2024C. The research method data collection techniques include questionnaires, interviews, observation, and documentation. The results of the study show that social media has two opposing sides. On the one hand, social media offers benefits such as easy access to academic information, facilitates group discussions, and provides additional learning resources that support the learning process. Students can take on educational and spiritual content to enrich their faith and knowledge. However, on the other hand, excessive use of social media has negative effects such as distraction, decreased concentration, reduced structured study time, and anxiety due to constant notifications. The habit of multitasking also makes students less disciplined in managing their study time. These findings confirm that social media can be either a support or a hindrance, depending on how students manage its use. Therefore, awareness and good time management are needed so that social media can be optimally utilized to support productive learning habits and build character on theology students.